2021
DOI: 10.15581/003.34.4.117-133
|View full text |Cite
|
Sign up to set email alerts
|

Spanish companies’ website communication of environmental, social, and governance information

Abstract: This study’s goal is to analyze the website communication of environmental, social, and governance –Environmental Social Governance (ESG)– information by companies on the Madrid Stock Exchange. The empirical descriptive and inferential analysis determines IBEX35 companies’ regulatory compliance in disclosure of non-financial information through examination of their website disclosure of ESG information. Economic-financial information from the Iberian Balance Sheet Analysis System (Sistema de Análisis de Balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Companies with the highest values for Indebtedness and ROA are more likely to obtain higher values for ESG, as are those with higher Liquidity and ROE. This conclusion coincides with the results obtained by [40]. We cannot conclude that the companies with the highest indebtedness and economic profitability and the highest levels of ESG disclosure also comply best with regulations and adapt best to achieving the objectives of the 2030 Agenda.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Companies with the highest values for Indebtedness and ROA are more likely to obtain higher values for ESG, as are those with higher Liquidity and ROE. This conclusion coincides with the results obtained by [40]. We cannot conclude that the companies with the highest indebtedness and economic profitability and the highest levels of ESG disclosure also comply best with regulations and adapt best to achieving the objectives of the 2030 Agenda.…”
Section: Discussionsupporting
confidence: 82%
“…Analyzing the web transparency of the non-financial information of the 65 listed companies on two European stock indexes, the German (DAX30) and the Spanish (IBEX35), Ref. [40] found a significant relationship between financial indicators (economic profitability and financial profitability) and the transparency of the non-financial indicators of said companies. In the same line [41] analyzed 314 UK-listed companies over the period 2002-2015 and found that companies periodically adjusted their level of commitment to society to meet their goal of publishing their corporate performance on their websites.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 pandemic has increased awareness of the risk of systemic problems and existential threats such as climate change to the stability of the financial system, as well as greater interest in ESG information. Some investors have therefore sought simpler ways to evaluate the problems of sustainable development through comparable and consistent metrics (Adams & Abhayawansa, 2022; Gutiérrez‐Ponce et al, 2021). Stakeholders demand that organizations provide more consistent, comparable ESG disclosure, and this demand has led to harmonization through internationally recognized sustainability standards.…”
Section: Literature Review and Development Of Rqsmentioning
confidence: 99%